Taxonomy and key for the identification of tuna species exploited from the Indian EEZ - Joshi, K. K.; Abdussamad, E. M.; Saidkoya, K.P.; Rohit, Prathibha; Ghosh, Shubhadeep; Sreenath, K.R.; Beni, M.; Bineesh, K. K.; Akhilesh, K.V. (Indian Journal of Fisheries, 2012)
Tuna samples were collected from the commercial landings at Kochi, Tuticorin, Mangalore, Visakhapatnam, Veraval andLakshadweep at regular intervals during 2006-2010. Detailed morphometric data, viz., height of dorsal and anal fins, eyediameter, snout length, head height and height of body were collected. Otoliths were collected from eight species andanalysed. Results indicated that structure and shape of the otoliths show species specific differences. Taxonomic details oftunas and tuna like species have been generated from the present as well as past studies and the species were redescribedwith color photographs and keys for identification. The species included Thunnus albacares (Bonnaterre, 1788), Thunnusobesus (Lowe, 1839), Thunnus tonggol (Bleeker, 1851), Sarda orientalis (Temminck & Schlegel, 1844), Katsuwonus pelamis(Linnaeus, 1758), Euthynnus affinis (Cantor, 1849), Auxis thazard (Lacepède, 1800), Auxis rochei (Risso, 1810) andGymnosarda unicolor (Rüppell 1836).